HUBUNGAN PEMBERIAN PENGGANTI AIR SUSU IBU (PASI) DENGAN STATUS GIZI BAYI DI UPT PUSKESMAS AEK NATOLU KECAMATAN LUMBAN JULU KABUPATEN TOBA TAHUN 2021 - Nolifhera Hudayati Manurung; Tetti Seriati Situmorang; Indra Agussamad (Pusat riset dan Inovasi Nasional, 2022)
Background: Nutritional problems that occur in early life have serious consequences. Underweight in children under five accounts for 4.7% of deaths or two million deaths from all deaths of children under five in the world. Mother's Milk Breast milk is the best food because it contains balanced and perfect nutrition for baby's growth and development. However, considering that when mothers are unable to breastfeed or can only breastfeed partially, there is a legitimate market for breast milk replacement products (PASI) for infants as an effort to fulfill infant nutrition. Methods: This research is a quantitative research with a correlational approach using a cross sectional design. This study aims to determine the relationship between the provision of breast milk substitutes with the nutritional status of infants at the UPT Puskesmas Aek Natolu, Lumban Julu District, Toba Regency in 2021. The population in this study were all infants aged 6 months in the working area of the UPT Puskesmas Aek Natolu as many as 32 babies. The sampling technique in this study was total sampling so that the number of samples was 32 infants. Data analysis was carried out by statistical tests using chi-square with a significance degree of = 0.05. Results: Most babies were not given PASI, as many as 22 people (68.7%) and a small portion were given PASI, namely 10 people (31.3%). Most of the reasons why babies were given PASI were recommended by family/friends as many as 5 people (50%), because 3 people did not get breast milk (30%) and a small part because the mother worked as much as 2 people (20%). Most of the baby's nutritional status is normal, as many as 25 people (78.1%.) and a small portion of the abnormal status is as many as 7 people (21.9%). The results of the chi square test obtained a p-value = 0.019, this value < 0.005, this means that there is a significant relationship between the provision of Breast Milk Substitutes (PASI) and the nutritional status of infants.